Intellect as the basis of future scientist's intellectual work culture - Sergeevna Kosmodemyanskaya, Svetlana (2020)
The relevance of the problem is due to the need for monitoring diagnoses of future scientist's intellectual work culture and insufficient study of various aspects of the multidimensional intelligence model as its basis. The purpose of the article is to consider the functional-structural model of multidimensional intellect as the basis of future scientists' intellectual work in the line of the human-anthropological approach and its approbation. The leading method of studying this problem is modeling, which allows us to study this problem as a process of mastering by future scientists the fundamental system qualities of intellectual work culture.